Investigating the Effects of Cognitive-Behavioral-Therapy-based Psychoeducation Program on University Students’ Automatic Thoughts, Perceived Stress, and Self-efficacy Levels - Veysel Kaplan; Mehmet Emin Düken; Rabia Kaya; Joseph Almazan (Journal of Research & Health, 2023)
Background: University life is a special period in which students take full responsibility for their lives, especially as individuals. This period includes many positive and negative situations. As a result, they need serious psychological support to cope with the potential or real problems they experience. This study aims to determine the effects of cognitive-behavioral-therapy-based psychoeducation programs on university students’ automatic thoughts, perceived stress, and self-efficacy levels. Methods: This was a quasi-experimental study with a single group pre-test and post-test design. The research was carried out at a university in Turkey from October 1 to November 15, 2022. The sample consisted of 223 students who agreed to participate in the research. The psychoeducation program prepared within the scope of the study was conducted face-to-face for four 45-min sessions. In this study, we used an individual introduction form, automatic thought questionnaire, perceived stress scale, and general self-efficacy scale. Data analysis was done via SPSS software, version 23. To analyze the data, we used descriptive statistics along with the Pearson correlation test and the Spearman correlation test. Results: A total of 73.4% of the students who participated in the research were female and 49.5% stayed in the student dormitory. The economic situation of 53.2% was moderate and 41.4% to 67.1% of the students had a good relationship with their families, while 63.5% had a good relationship with their friends. After the psychoeducation, a significant decrease was observed in the mean scores of students’ automatic thoughts and perceived stress, while their self-perception scores increased significantly (P<0.05). Conclusion: The cognitive-behavioral-therapy-based psychoeducation program positively affects university students in various aspects. After the psychoeducation, the perceived stress levels of the students decreased, their self-efficacy levels were positively affected, and their negative automatic thinking levels decreased.